OPTIMALISASI PERAN ZAKAT DALAM MENGENTASKAN KEMISKINAN DI INDONESIA (UINSI Samarinda, 2012)
Zakat is a system unique in the history of humanity that only exist in Islam. Zakat is not only about worship but includes the financial system, economic, social, political as well as moral. Zakat has the function of the economy in alleviating poverty charity even give a significant influence on the macro economy. BAZNAS stated that the potential of zakat in Indonesia is estimated to reach Rp 217 fantastic trillion a year but in 2011 newly collected Rp. 1.8 Trillion. Potential of zakat which are yet to be excavated to the maximum so that has not been able to alleviate poverty in Indonesia because of a lack of professional management. Here the role of the state is required in managing zakat. This role can be achieved if there is a reorientation of the understanding and management of zakat zakat zakat can be empowered to be optimal. It needs a dynamic synergy between government and society in optimizing alms role in alleviating poverty in Indonesia.